Design and applications of liposome-in-gel as carriers for cancer therapy. (31st December 2022) - Mou, Yixuan; Zhang, Pu; Lai, Wing-Fu; Zhang, Dahong
Abstract: Cancer has long been a hot research topic, and recent years have witnessed the incidence of cancer trending toward younger individuals with great socioeconomic burden. Even with surgery, therapeutic agents serve as the mainstay to combat cancer in the clinic. Intensive research on nanomaterials can overcome the shortcomings of conventional drug delivery approaches, such as the lack of selectivity for targeted regions, poor stability against degradation, and uncontrolled drug release behavior. Over the years, different types of drug carriers have been developed for cancer therapy. One of these is liposome-in-gel (LP–Gel), which has combined the merits of both liposomes and hydrogels, and has emerged as a versatile carrier for cancer therapy. LP–Gel hybrids have addressed the lack of stability of conventional liposomes against pH and ionic strength while displaying higher efficiency of delivery hydrophilic drugs as compared to conventional gels. They can be classified into three types according to their assembled structure, are characterized by their nontoxicity, biodegradability, and flexibility for clinical use, and can be mainly categorized based on their controlled release, transmucosal delivery, and transdermal delivery properties for anticancer therapy. This review covers the recent progress on the applications of LP–Gel hybrids for anticancer therapy.